2007
DOI: 10.1073/pnas.0610535104
|View full text |Cite
|
Sign up to set email alerts
|

BIG1, a brefeldin A-inhibited guanine nucleotide-exchange protein, is required for correct glycosylation and function of integrin β1

Abstract: Glycosylation of ␤1 integrin (␤1) in the Golgi complex has been related to its function in multiple cell processes, e.g., invasiveness, matrix adhesion, and migration. Brefeldin A-inhibited guanine nucleotide-exchange proteins (BIG) 1 and BIG2 activate human ADP-ribosylation factors (ARF) 1 and ARF3 by catalyzing the replacement of ARF-bound GDP with GTP to regulate Golgi vesicular transport. We show here a requirement for BIG1 (but not BIG2) in glycosylation and function of ␤1. In HepG2 cells treated for 48 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
(45 reference statements)
5
31
1
Order By: Relevance
“…Phosphorylation of β-catenin clearly influenced its intracellular distribution (1,3), and reversible O-glycosylation may affect its nuclear accumulation and transcriptional action (64)(65)(66). Correct N-glycosylation and trafficking of integrin β1 required BIG1 (30) and BIG2 (28), respectively, but their roles in O-glycosylation are unknown. We speculate that accumulation of β-catenin at Golgi structures after BIG1 or BIG2 depletion contributes to inhibition of Wnt signaling by delaying β-catenin transit to and action in nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of β-catenin clearly influenced its intracellular distribution (1,3), and reversible O-glycosylation may affect its nuclear accumulation and transcriptional action (64)(65)(66). Correct N-glycosylation and trafficking of integrin β1 required BIG1 (30) and BIG2 (28), respectively, but their roles in O-glycosylation are unknown. We speculate that accumulation of β-catenin at Golgi structures after BIG1 or BIG2 depletion contributes to inhibition of Wnt signaling by delaying β-catenin transit to and action in nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, BIG1 was seen mainly at the trans-Golgi network (TGN), sometimes partially overlapping BIG2, which was associated also with recycling endosomes (24-26), e.g., in moving proteins and lipids among TGN, endosomes, and cell surface (24,(27)(28)(29). Although actions of BIG1 and BIG2 at the TGN were described as "redundant" (27), each protein clearly has specific roles in moving proteins and lipids that are not shared with the other (24,30,31). Overexpression in cultured cells of mutant BIG2 lacking Arf GEF activity markedly altered intracellular distributions of E-cadherin and β-catenin (32).…”
mentioning
confidence: 99%
“…BIG1 is often found at trans-Golgi membranes (16,17); after BIG1 depletion, membranes of the HepG2 cell Golgi trans face appeared less smooth by electron microscopy with more vesicle-like structures (18). Boal and Stephens also reported that Golgi structure was altered after BIG1 depletion (19).…”
mentioning
confidence: 92%
“…Alternatively, the well characterized brefeldin A-sensitive GEFs may be upstream regulators of Arf1 in this signaling pathway. In fact, BIG1 mediates migration of HepG2 cells (40), and BIG2 promotes neural progenitor cell migration in the cerebral cortex (41). It will be interesting to study how the GEFs for Arf1 and/or Arf6 cooperatively regulate 3T3-L1 cell migration.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%